Pediatric Cerebral Stroke: Susceptibility-Weighted Imaging May Predict Post-Ischemic Malignant Edema. Issue 5 (October 2013) - Bosemani, Thangamadhan; Poretti, Andrea; Orman, Gunes; Meoded, Avner; Huisman, Thierry A.G.M.
Susceptibility-weighted imaging (SWI) is an advanced MRI technique providing information on the blood oxygenation level. Deoxyhemoglobin is increased in hypoperfused tissue characterized by SWI-hypointensity, while high oxyhemoglobin concentration within hyperperfused tissue results in a SWI iso- or hyperintensity compared to healthy brain tissue. We describe a child with a stroke, where SWI in addition to excluding hemorrhage and delineating the thrombus proved invaluable in determining regions of hyperperfusion or luxury perfusion, which contributed further to the prognosis including an increased risk of developing post-ischemic malignant edema.